Fukushima Daiichi fuel debris simulant materials for the development of cutting and collection technologies. Issue 9 (2nd September 2018) - Journeau, Christophe; Roulet, Damien; Porcheron, Emmanuel; Piluso, Pascal; Chagnot, Christophe
ABSTRACT: Cutting fuel debris (solidified corium) is an important issue for the decommissioning of Fukushima Daiichi Power Station. The main reasons for developing and using suel debris simulants are presented. The relative merits of various types of materials (stainless steel, zircalloy, sintered ceramic, cast-fused zirconia, metal + ceramic, melted inactive simulants, prototypic fuel debris, irradiated fuel debris simulant) that can be used to test debris cutting have been assessed against criteria relevant for the cutting technique itself and also for (radioactive) aerosol and combustible gas generation. Simplified simulants can be used for the development of fuel debris cutting techniques but have limited representativeness so that melted inactive fuel debris simulant must be used to assess the cutting performance. Concerning combustible gas generation, zirconium plates provide an upper bound in term of underwater generation of hydrogen. Finally, for aerosol and dust generation, it appears that non-radioactive simulant cannot correctly represent the aerosol formed during cutting but prototypic fuel debris simulants, using depleted uranium are required. Laser cutting tests have been carried out with several types of simulant materials. Promising results were achieved in term of cutting ability both in air and underwater. Data have also been collected on the released aerosols. Nevertheless, confirmatory experiments with prototypic debris are still needed.